Menakar Kasus Lumpur Lapindo Sebagai Pelanggaran - Putra, Hananda Dwi Sasongko; Adyatma, Arief Dwi; Ahmad, Muh. Jufri (JHP17 (Jurnal Hasil Penelitian), 2020)
The factor of the Lapindo mudflow disaster led to errors in the planning and drilling process whichsucceeded in eliminating the settlement of communities around drilling. The impact felt by the victims afterthe incident in the refugee camp was very alarming, because it was far from feasible. There are many rightsthat have been violated in the case of Lapindo mud so that the state is obliged to intervene in resolving thiscase. So that the process that has occurred so far from the beginning until now regarding the subject matterof the core problem remains the same, namely the conflict between victims of Lapindo mudflow and PTLapindo due to the retraction of the compensation process that is considered too small or not equivalent tothe losses suffered by Lapindo mud victims. In addition to the problem, namely the rejection of therelocation of Lapindo mudflow victims, the construction of damaged infrastructure due to Lapindomudflows and the widespread spread of Lapindo mudflows has not yet been completed. So this incidentraises the question of whether the Lapindo mudflow is a crime or a violation of human rights. As well ashow the state has obligations to this case. This study uses a juridical normative approach whose researchresults show that this case is a violation of human rights and the state is obliged to restore the condition ofthe victim and the environmental impact caused and the state must thoroughly manage compensation orcompensation arising from Lapindo mud